KETERPADUAN KOMPONEN PENGEMBANGAN PARIWISATA KOTAGEDE SEBAGAI KAWASAN WISATA BUDAYA BERKELANJUTAN - Nirmana Adhelia; Soedwiwahjono Soedwiwahjono; Galing Yudana (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2015)
Kotagede as the capital city of the former Mataram Islam kingdom has potential culture and history tourism which places in two different areas, Yogyakarta City  and Bantul region. It needs contribution between Yogyakarta government, local government and local communities to protect Kotagede. The development of tourism activities also need support from all stakeholder to make the tourism sustain. Therefore, this research was conducted to determine the level of integration of tourism development components as the area of sustainable cultural tourism in Kotagede. The method of research is deductive-quantitative, while the data analisys technique used is  descriptive analysis of quantitative, scoring and crosstab analysis. Results from this study is Kotagede judged to have met the criteria as a sustainable cultural tourism area with an integrated component of tourism development. However, when viewed from the stakeholder cooperation that occurred in the development of tourist areas, Kotagede showed a low value. Thus, although the components of tourism development Kotagede shows the alignment of sustainability, but the resulting relationship is still weak. Keywords:cultural tourism area, integrated tourism, sustainable tourism, tourism